2012
DOI: 10.1016/j.pmrj.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐Articular Hip Injections Using Ultrasound Guidance: Accuracy Using a Linear Array Transducer

Abstract: This retrospective review suggests that physicians who use a linear array transducer can accurately perform intra-articular hip injections in an outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 6 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…The authors found four level 1 studies for US-guided hip injections with a mean accuracy of 99% and range of 97–100%; these four studies were also included in our review 11 13 16 18. The two studies they classified as level 4 and 5 were excluded from our paper 21 22. Their review also identified two level 2 studies for landmark-guided hip injections with a mean accuracy of 73% and a range of 67–73% 12 19.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found four level 1 studies for US-guided hip injections with a mean accuracy of 99% and range of 97–100%; these four studies were also included in our review 11 13 16 18. The two studies they classified as level 4 and 5 were excluded from our paper 21 22. Their review also identified two level 2 studies for landmark-guided hip injections with a mean accuracy of 73% and a range of 67–73% 12 19.…”
Section: Discussionmentioning
confidence: 99%
“…In both cadaveric models and the clinical setting, sonographically guided hip joint injections have been reported 97% to 100% accurate (53,61,73,95). In both cadaveric models and the clinical setting, sonographically guided hip joint injections have been reported 97% to 100% accurate (53,61,73,95).…”
Section: Hip Jointmentioning
confidence: 99%
“…A majority of the studies (49/57 (86%))6 7 9 11–13 15 17–25 27–30 32–51 53–61 evaluated injections in a single joint, whereas 14% (8/57)5 8 10 16 26 31 52 55 assessed injections in more than one joint. Thirty-five per cent (20/57) of the studies evaluated knee injections,8–10 13 15 16 19–23 26 31 32 36 37 48 52 56 57 46% (26/57) evaluated glenohumeral (GH) joint injections,5 7 8 10 11 15–17 24–26 28 29 31 38–40 42 43 46 47 49 52 54 60 61 21% (12/57) evaluated hip injections8 12 27 30 33 35 41 44 45 50 52 59 62 and 4% (2/57) evaluated sacroiliac (SI) joint injections 18 34. Four studies (7%) assessed injections in the ‘shoulder’, but did not specify which shoulder structure or joint they were injecting 6 53 55 58…”
Section: Resultsmentioning
confidence: 99%
“…The level of evidence for a majority of the studies evaluating major joint USGI accuracy (15/23 (65%))5 8 9 15 16 18 20 21 23 27 30 32 34 36–39 41 42 44–46 49 or LMGI accuracy (28/28 (100%))5 7 9–13 17 19 21–26 28 31 32 36–38 40 43 47 48 50 60 61 were level 1 or 2. The mean accuracy of GH, hip and knee joint USGIs in studies with level 1 or 2 evidence ranged from 91% to 100%,5 8 9 15 18 21 23 32 36–39 42 46 49 whereas the mean accuracy of LMGIs were between 64% and 81% 5 7 9–13 17 19 21–26 28 31 32 36–38 40 43 47 48 50 60 61.…”
Section: Resultsmentioning
confidence: 99%